A hydrogel electrolyte high local area electrochemical polishing method
Patent Information
- Application Number
- CN202611210851.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-10-30
AI Technical Summary
微射流/毛细管电解液局域供给技术通过微小喷嘴在局部形成电解液流场或液膜,核心局限在于液体的毛细效应与表面张力导致电解液在工件表面不可控铺展,加工区域边界模糊
[0034]本发明所提供的一种水凝胶电解质高定域性电化学抛光方法,相较于现有电化学抛光技术,具有以下显著的有益效果:
Smart Images

Figure CN123000131A_ABST
Abstract
Description
Technical Field
[0001] This invention proposes a hydrogel electrolyte highly localized electrochemical polishing method, which belongs to the field of electrochemical processing. Technical Background
[0002] In the field of high-precision manufacturing, polishing technology is undergoing a profound transformation from achieving macroscopic surface smoothness to selectively removing materials with high locality. The rapid development of aerospace components such as blades and disks, micro-medical devices, and precision optical components has created an urgent need for precision shaping and polishing with high locality on complex curved surfaces or devices. This "high locality" processing goal not only requires extremely high spatial resolution but also zero interference to non-target areas during the processing.
[0003] Electrochemical polishing, due to its atomic-level layer-by-layer removal characteristics without macroscopic stress and heat-affected zones, is considered an ideal path to achieve high surface integrity. Traditional electrochemical polishing relies on liquid electrolytes, leveling the surface by the difference in dissolution rates between microscopic protrusions and depressions on the anode surface. When attempting localized polishing with micro-electrodes, the thin liquid film formed by the electrolyte on the surface spreads rapidly through capillary action, resulting in a reaction area much larger than the electrode geometry, forming "stray corrosion" edges. Traditional electrochemical polishing often involves surface insulation treatment in non-polished areas; however, the high-speed scouring of the electrolyte and the heat generated during processing place high demands on the fabrication process of the insulating coating, often exacerbating the complexity of localized polishing. Furthermore, the effectiveness of traditional electrochemical polishing is affected by mass transfer conditions. The presence of flowing electrolyte disrupts the stability and spatial variability of the diffusion layer, weakening the differences in mass transfer conditions between depressions and protrusions. This prevents the electrochemical system from sensitively "sensing" and "responding" to microscopic morphological fluctuations, thus limiting its planarization capability and accuracy. Uneven flow velocity distribution on the anode surface also leads to a decrease in polishing quality.
[0004] In the field of electrochemical machining, the pursuit of highly localized polishing has spurred the development of various localized electrochemical polishing techniques, mainly including methods based on microfluidic / microcapillary electrolyte local supply, insulating mask masking, and microprobe near-field scanning. Microfluidic / capillary electrolyte local supply technology forms an electrolyte flow field or liquid film locally through tiny nozzles. Its core limitation lies in the capillary effect and surface tension of the liquid, causing uncontrollable spreading of the electrolyte on the workpiece surface and blurring the boundaries of the processing area. Insulating mask masking technology has limitations: perfect microscopic adhesion between the mask and the workpiece surface is difficult to achieve, allowing electrolyte to seep into micro-gaps and causing "stray corrosion"; an electric field distortion zone forms below the mask edge, resulting in rounded edge transitions; the process steps are cumbersome, and the mask itself may contaminate the workpiece or require complex cleaning. The limitations of microprobe near-field scanning technology lie in the extreme difficulty of maintaining a stable nanoscale processing gap; vibration or surface undulations can easily lead to short circuits or gap instability; the processing efficiency is extremely low, suitable only for point or line features; and reaction products accumulate rapidly in a confined space, causing process instability. Furthermore, these technologies do not escape the framework of "liquid electrolytes," and mass transfer conditions still affect the polishing quality.
[0005] The existing patent application, "A Method for Dynamically Controlling Electrochemical Polishing Using an Energy Storage Electrode and Its Application" (Patent Application Publication No.: CN120519947A), utilizes an energy storage electrode with a multi-dimensional nanoarray surface morphology. During electrochemical polishing, when the potential and current density of the working fluid are in the overpassivation range, a negative polarity pulse is emitted to cause the energy storage electrode to store charge; when the potential and current density of the working fluid are in the active dissolution range, a positive polarity pulse is emitted to cause the energy storage electrode to release charge. Through precise control of its surface charge storage and release characteristics, directional and precise polishing of nanoscale materials is achieved. In comparison, this patent proposes a highly localized electrochemical polishing method for quasi-solid hydrogels. The processing flow is simpler, and no liquid polishing medium is involved in the process, fundamentally eliminating stray corrosion. Furthermore, this invention eliminates the influence of workpiece surface flow velocity distribution on polishing quality, resulting in better polishing consistency and quality.
[0006] Existing patent application "Polishing Component and Chemical Polishing Equipment for Generating Micro-Electrostatic Fields" (Patent Application Publication No.: CN105405791A) proposes a polishing component under the action of a micro-electrostatic field. This component is positioned above a polishing machine platform and includes an electric field generating unit and a polishing pad. The electric field generating unit generates a micro-electrostatic field by receiving an applied voltage, and this micro-electrostatic field is applied to the polishing area of the polishing pad. This patent achieves localized chemical polishing by limiting the polishing area through the generation of a micro-electrostatic field. Compared to other methods, this patent does not involve liquid polishing media during processing, resulting in higher localization and a simpler processing flow. It also offers higher processing efficiency and better processing results for surfaces with high initial roughness.
[0007] The existing patent application, "A Method for Laser-Jet Electrochemical Hybrid Polishing" (Patent Application Publication No.: CN115305560A), proposes a laser-jet electrochemical hybrid polishing method. This method primarily utilizes laser irradiation combined with the electrolytic jetting of an electrolyte to treat stainless steel surfaces. It offers significant flexibility, enabling selective polishing of large, irregularly shaped workpieces in everyday environments. However, due to the uncontrollable spread of the electrolyte on the workpiece surface, the boundaries of the processed area are relatively blurred. In contrast, this invention does not use a liquid polishing medium, resulting in a clearer processed area, higher localization accuracy, and elimination of the influence of turbulent flow fields on the polishing quality, leading to higher polishing consistency and uniformity.
[0008] Existing patent application "A Bimetallic Composite Plate Electrolytic Polishing Cathode and Method" (Patent Application Publication No.: CN121653807A) proposes a bimetallic composite plate electrolytic polishing cathode. During processing, sodium nitrate electrolyte is introduced into the processing area, while deionized water is introduced into the unprocessed area. The two work synergistically to precisely limit the electrolytic reaction to the target processing area. Compared to this patent, this patent utilizes the near-solid-state properties of hydrogel electrolytes to strictly confine the processing area to the region where the workpiece contacts the hydrogel, resulting in higher localization accuracy and clearer processing boundaries.
[0009] The existing patent application, "Integrated Device and Implementation Method for Localized Electropolishing with Laser Enhancement and Reciprocating Vibration Synergy" (Patent Application Publication No.: CN118848140A), proposes an integrated device for localized electropolishing with laser enhancement and reciprocating vibration synergy. This device enhances the energy density of the processing area through the synergistic coupling of laser irradiation and electrochemical dissolution, achieving the purpose of localized electropolishing. Compared to this patent, this patent has a simpler processing technology, does not involve complex coupling issues, and does not involve liquid electrolytes during processing, fundamentally solving the problem of stray corrosion and exhibiting excellent localization.
[0010] Existing patent application "System and Method for Improving the Localization of Electrolytic Machining of Array Micropits with Flexible Templates" (Patent Application Publication No.: CN104551282A) employs a flexible template. Through a forward-flow electrolytic machining method, a tight fit between the workpiece and the template is achieved. The high-speed electrolyte impact on the flexible template causes deformation at the hole edges, effectively protecting the micropit edges, reducing stray corrosion at the micropit edges, and improving the localization of electrolytic machining. Patent application "A Device and Method for Electrolytic Machining with Particle-Assisted Masking" (Patent Application Publication No.: CN111515480A) uses a step-by-step process of "substrate pretreatment - anode substrate mask fabrication - particle-assisted electrolytic machining". The patents have improved the localization of the machining process. For example, the patent application "System and Method for Electrolytic Machining of Micro-pit Arrays Based on Magnetic PDMS Mask" (Patent Application Publication No.: CN106064261A) uses a magnetic field to control a magnetic PDMS mask, ensuring it adheres tightly to the surface of the anode workpiece, thus improving the localization of the micro-pit array in electrolytic machining. Another patent application, "A Method for Electrolytic Machining Microstructures Based on Coated Porous Polymer Mask" (Patent Application Publication No.: CN113458513A), proposes a porous polymer mask. A polymer solution prepared from polystyrene-b-polyacrylic acid and the organic solvent CS2 is coated onto the workpiece surface, and the mask is obtained after cooling. These patents improve the masking process through various methods, ensuring close adhesion to the workpiece, thereby enhancing the localization of electrolytic machining. Compared to these patents, the solid-state electrolyte proposed in this patent eliminates the mask fabrication process, simplifying the machining flow. Furthermore, its machining effect is unaffected by the mask fabrication process, avoiding "stray corrosion" caused by electrolyte seepage through the mask's micro-gap, resulting in higher machining stability and localization accuracy.
[0011] With the development of electrochemical polishing technology, many studies on solid polishing electrolytes have emerged. Patent application "A solid particle for solid electrolytic polishing of metal" (patent application publication number: CN118186562A) proposes a solid particle for solid electrolytic polishing. The average pore size of the porous solid particle is ≤20nm. The porous solid particle absorbs the electrolyte and transfers charge to achieve electrochemical polishing. Patent "A solid medium electrochemical polishing method with controllable material removal rate" (patent publication number: CN116084002B) proposes a solid medium electrochemical polishing method with controllable material removal rate. It uses solid particles containing electrolyte as a conductive medium. During the polishing process, the electrolyte content in the solid particles is adjusted to generate different current densities between the polished part and the cathode, so as to control the material removal rate of the polishing process and thus adapt to the polishing of surfaces with different roughness. Patent application "A magnetic field assisted dry electrochemical polishing device and method for the inner surface of pipes" (patent application publication number: CN121295318A) applies the above-mentioned solid electrolyte to the polishing of the inner surface of pipes and introduces magnetic field assisted ion migration. Such solid electrolytes cannot be used for localized electropolishing, and additional insulation treatment is still required when performing localized electropolishing. In contrast to these patents, the hydrogel used in this patent is a near-solid state, with no liquid polishing medium involved in the processing. Localized polishing can be performed without insulation treatment, resulting in a simple process and high localization accuracy.
[0012] In recent years, interdisciplinary research has provided new avenues for technological breakthroughs. Hydrogels, as a type of solid-like, intelligent, responsive electrolyte, possess a three-dimensional network structure that can retain a large amount of water, allowing ion transport and ensuring the smooth occurrence of electrochemical reactions. As a solid-like polishing medium, hydrogels exhibit excellent localization; the processing area is strictly and uniquely defined by the geometric area of the "hydrogel-anodic contact interface," fundamentally solving the problems of poor localization and uniformity caused by electrolyte diffusion in traditional liquid-based polishing. Furthermore, the absence of flowing electrolytes during processing almost completely eliminates the influence of convection and uneven flow velocity distribution; mass transport relies solely on ion migration and diffusion, maximizing the difference in diffusion conditions between depressions and protrusions. In addition, hydrogels, as electrolytes, possess strong programmability; their properties can be altered by controlling monomer structure or composition, or by adding specific functional fillers, to meet actual processing requirements.
[0013] Existing patent applications, such as "A Conductive Hydrogel and Its Preparation Method and Application" (Publication No.: CN121159884A), describe how amino-based natural polymers are grafted with dopamine-based oxidized hydroxycarboxylic acid natural polymers to form a first dynamic network via a Schiff base reaction. Metal ions then form a second dynamic network by chelating with active functional groups in the system to create metal-ionic bonds. Combined with hydrogen bonding within the system, this endows the hydrogel with excellent conductivity and mechanical strength. Patent application "A Sprayable Dual-Network Hydrogel Microsphere Adhesive and Its Preparation Method and Application" (Patent Application Publication No.: CN121154893A) proposes a sprayable dual-network hydrogel microsphere adhesive that improves its toughness by constructing a dual-network structure. Patent "A Method for Preparing a Hydrogel Chip with a Dendritic Channel Structure" (Patent Publication No.: CN108890937B) uses a template method to prepare a hydrogel chip with a dendritic channel structure through secondary casting of the hydrogel. These patents demonstrate the strong programmability of hydrogels, allowing processing requirements to be met by changing the corresponding components and structure.
[0014] In summary, in order to achieve highly localized dissolution of workpiece surface materials and further improve polishing quality, this patent combines knowledge from interdisciplinary fields such as electrochemistry, organic chemistry, and materials science to propose a hydrogel electrolyte highly localized electrochemical polishing method. Summary of the Invention
[0015] This invention aims to achieve highly localized electrochemical polishing of materials and proposes a hydrogel electrolyte highly localized electrochemical polishing method. This method replaces the traditional liquid polishing medium with a solid-like hydrogel. Ion transport is achieved through the three-dimensional network within the hydrogel, strictly confining the electrochemical reaction to the localized area where the hydrogel contacts the workpiece, thereby achieving highly localized electrochemical polishing of the workpiece.
[0016] Technical solution
[0017] A highly localized electrochemical polishing method using hydrogel electrolytes is characterized by its core idea of replacing traditional liquid polishing media with a solid-like hydrogel, utilizing the three-dimensional network structure within the hydrogel as an ion transport channel. During processing, the hydrogel is in close contact with the anode and cathode interfaces, with the cathode connected to the negative terminal of the power supply and the anode connected to the positive terminal. Due to the solid-like properties of the hydrogel, the electrochemical reaction is strictly confined to the localized area where the hydrogel contacts the workpiece, and the anode material within the processing area dissolves due to the electrochemical reaction. Dissolution products readily diffuse and react quickly at microscopic protrusions on the workpiece, while products accumulate significantly at depressions due to longer diffusion paths, resulting in a slower reaction rate. This difference in dissolution rates leads to the leveling of the anode surface, thereby achieving highly localized electrochemical polishing of the workpiece.
[0018] The technical solution of this method mainly includes the following steps:
[0019] (I) Construction of hydrogel electrolytes:
[0020] (1.1) The hydrogel monomers are mixed with a crosslinking agent and subjected to freeze-thaw cycles at low temperature. The monomer molecules will polymerize under the action of the crosslinking agent, and the hydrogel will be obtained after solidification. The hydrogel has a three-dimensional network structure inside, which allows ion transport and ensures the smooth occurrence of electrochemical reactions.
[0021] (1.2) Dense internal microchannels are fabricated in the solidified hydrogel using laser etching, UV lithography, and other methods. These dense microchannels allow acidic solutions to flow slowly through, ensuring that the precipitate generated during the processing is in full contact with the acidic solution.
[0022] (ii) Highly localized electrochemical polishing
[0023] (2.1) Place the hydrogel electrolyte between the anode and cathode, and use the pressure applied by the machine tool spindle to make the hydrogel and the anode and cathode interface fit tightly together. Adjust the position of the spindle to make the hydrogel and the anode and cathode interface in the best contact state.
[0024] (2.2) The cathode is connected to the negative terminal of the power supply and the anode is connected to the positive terminal of the power supply. Due to the solid-like properties of the hydrogel electrolyte, the processing area is strictly limited to the contact area between the anode interface and the hydrogel. The anode material in the processing area dissolves due to electrochemical reaction.
[0025] (2.3) Under the influence of an applied electric field, the anode dissolves, and metal ions enter the solution and migrate towards the cathode; a hydrogen evolution reaction occurs at the cathode, generating hydroxide ions, which migrate towards the anode. The metal ions combine with the hydroxide ions to form a precipitate, hindering the electrochemical reaction.
[0026] (2.4) Injecting an acidic solution into the microchannels inside the hydrogel will dissolve and remove the precipitate in the hydrogel, allowing the electrochemical reaction to continue and completing the highly localized electrochemical polishing of the anode workpiece.
[0027] Furthermore, the spatial constraint of the electrochemical reaction is achieved by using a solid-like hydrogel electrolyte; the hydrogel is a network structure formed by cross-linking of hydrophilic polymer chains, which contains a large number of three-dimensional network structures to provide channels for ion migration.
[0028] Furthermore, due to the solid-like properties of the hydrogel, the electrochemical reaction is strictly confined to the local area where the hydrogel contacts the workpiece. During processing, the hydrogel is in close contact with the anode and cathode interfaces, with the cathode connected to the negative terminal of the power supply and the anode connected to the positive terminal. The anode material dissolves due to the electrochemical reaction. The dissolution products at the microscopic protrusions of the workpiece are easy to diffuse and the reaction rate is relatively fast, while the products at the depressions are severely accumulated due to the long diffusion path and the reaction rate is relatively slow. The difference in the dissolution rates of the two leads to the leveling of the anode surface.
[0029] Furthermore, during the processing, it is necessary to ensure that the hydrogel adheres tightly to the anode and cathode. Therefore, the hydrogel should have good mechanical strength and toughness. The mechanical properties of the hydrogel can be improved by constructing a dual network structure, increasing the crosslinking density, and using composite nanomaterials.
[0030] Furthermore, the hydrogel is a three-dimensional network formed by hydrophilic monomeric polymer chains interconnected through cross-linking points, providing channels for ion migration; conventional hydrogels have low conductivity and cannot meet the requirements of electrochemical polishing; the hydrogel improves its conductivity through methods such as polymerizing conductive monomers, composite conductive fillers, and conductive ion permeation.
[0031] Furthermore, the anode and cathode interfaces are tightly bonded to the hydrogel electrolyte under the pressure of the machine tool spindle, ensuring the smooth progress of the electrochemical reaction. The spindle pressure should be less than the hydrogel's maximum withstand pressure, ensuring tight bonding between the hydrogel and the anode / cathode interfaces, to avoid damage to the hydrogel. The spindle pressure should not be too high or too low. Excessive pressure can easily damage the hydrogel, while insufficient pressure will result in poor bonding between the hydrogel and the anode / cathode interfaces, hindering the electrochemical reaction. The actual pressure value is monitored using a machine tool spindle force sensor, allowing for fine-tuning of the spindle position to achieve optimal contact between the hydrogel and the anode / cathode interfaces.
[0032] Furthermore, during the processing, metal ions generated at the anode enter the hydrogel and migrate towards the cathode. The hydrogen evolution reaction at the cathode generates hydroxide ions, which migrate towards the anode. The metal ions and hydroxide ions form precipitates inside the hydrogel, hindering the continued electrochemical reaction. The hydrogel has dense micro-channels inside. During the processing, an acidic solution is injected into the channels to dissolve the precipitates and carry them out of the hydrogel.
[0033] Beneficial effects:
[0034] The hydrogel electrolyte high localization electrochemical polishing method provided by this invention has the following significant advantages compared with existing electrochemical polishing techniques:
[0035] 1. A breakthrough has been achieved in processing localization and process stability. The most core contribution of this invention lies in using hydrogel to replace the free-flowing electrolyte, physically confining the electrochemical reaction space within the solid-solid interface of the hydrogel-workpiece contact, fundamentally eliminating stray corrosion in other areas, eliminating the need for insulation treatment of unprocessed areas, reducing the complexity of the process, and improving processing stability.
[0036] 2. The impact of mass transfer conditions on polishing quality is weakened, further improving polishing quality. Due to the near-solid-state properties of hydrogels, there is no flowing electrolyte during the process, almost completely eliminating the influence of convection during processing. Mass transport relies solely on ion migration and diffusion, improving the stability and spatial uniformity of the diffusion layer. The differences in mass transfer conditions between depressions and protrusions are enhanced, improving its leveling ability and precision, and avoiding the phenomenon of uneven flow velocity distribution on the anode surface, thus obtaining a highly consistent smooth surface.
[0037] 3. Significantly simplifies the system complexity and environmental burden of polishing. This invention eliminates the large and complex electrolyte circulation, temperature control, and waste gas and liquid treatment systems. The polishing medium is a near-solid-state, biodegradable hydrogel, achieving near-zero waste liquid discharge in green manufacturing from the source. Compared to traditional liquid electrochemical polishing, using a near-solid-state hydrogel for electrochemical polishing is less harmful to the environment and human health, and is more in line with the concept of green manufacturing. Attached Figure Description
[0038] Figure 1 This is a diagram illustrating the process of fabricating hydrogel electrolytes;
[0039] Figure 2 This is a schematic diagram of the electrochemical polishing and leveling process of hydrogel electrolyte;
[0040] Figure 3 This is a schematic diagram of the process of precipitation, dissolution, and discharge within the hydrogel;
[0041] Figure 4 This is a schematic diagram of the principle of a hydrogel electrolyte highly localized electrochemical polishing method;
[0042] Labels and names in the figure: 1. Hydrogel electrolyte; 1-1. Monomer molecule; 1-2. Crosslinking agent; 1-3. Functional filler; 2. Anode workpiece; 3. Cathode; 4. Machine tool spindle; 5. Power supply. Detailed Implementation
[0043] To make the objectives, technical solutions, and effects of this invention clearer and more explicit, the following examples provide a more detailed description of the invention. It should be noted that the specific embodiments described herein are merely illustrative and not intended to limit the scope of the invention.
[0044] The process of the present invention will now be described in detail with reference to the accompanying drawings:
[0045] according to Figure 1 As shown, the construction process of the hydrogel mainly consists of two steps: Step 1, monomer molecule 1-1 and crosslinking agent 1-2 are mixed and subjected to freeze-thaw cycles at low temperature to solidify and obtain hydrogel 1. The properties of the hydrogel are modified by changing the type of monomer molecule 1-1 and adding functional filler 1-3 to meet processing requirements. Step 2, dense microchannels are constructed inside the hydrogel using methods such as laser etching and UV lithography to inject acidic solutions during processing, dissolving and removing precipitates.
[0046] according to Figure 2 As shown, the principle of hydrogel electrolyte electrochemical polishing is as follows: During the processing, the hydrogel 1 electrolyte is in close contact with the surface of the anode workpiece 2. The electric field and electrochemical reaction are strictly confined within the contact area between the hydrogel 1 and the anode workpiece 2. The dissolution products at the microscopic protrusions of the anode workpiece 2 diffuse easily, and the reaction continues. At the depressions, the products accumulate severely due to the long diffusion path and high resistance, thus inhibiting the reaction rate at those locations. The difference in dissolution rates between the protrusions and depressions ultimately leads to the smoothing of the rough surface of the workpiece.
[0047] according to Figure 3 As shown, the anode workpiece 2 material dissolves, and metal ions enter the hydrogel 1 and migrate towards the cathode 3. A hydrogen evolution reaction occurs at the cathode 3, producing hydroxide ions, which migrate towards the anode workpiece 2. Free hydroxide ions and metal ions combine in the hydrogel to form a precipitate, hindering the continued electrochemical reaction. Free hydrogen ions from the acidic solution within the microchannel enter the hydrogel 1, dissolving the precipitate. The resulting free metal ions enter the acidic solution and are discharged with the solution, allowing the electrochemical reaction to continue.
[0048] according to Figure 4 As shown, the process includes the following steps:
[0049] Step 1: Mix monomer molecule 1-1 and crosslinking agent 1-2, and perform freeze-thaw cycles at low temperature. After solidification, hydrogel 1 is obtained. By selecting different types of monomer molecules 1 and adding different functional fillers 1-3, hydrogel 1 that meets processing requirements can be obtained.
[0050] Step 2: For the solidified hydrogel 1, internal microchannels are processed by means of laser etching, UV lithography and other methods to ensure that the acidic solution can be smoothly injected into the hydrogel during the processing.
[0051] Step 3: Place the hydrogel 1 electrolyte between the anode and cathode, and use the pressure applied by the machine tool spindle 4 to make the hydrogel 1 and the anode and cathode interface fit tightly together. Adjust the position of the spindle 4 to make the hydrogel 1 and the anode and cathode interface in the best contact state.
[0052] Step 4: Connect cathode 3 to the negative terminal of power supply 5, and anode workpiece 2 to the positive terminal of power supply 5. Under the influence of the applied electric field, anode workpiece 2 dissolves, and metal ions enter the solution and migrate towards cathode 3; hydrogen evolution reaction occurs at cathode 3, generating hydroxide ions, which migrate towards anode workpiece 2. The metal ions combine with hydroxide ions to form a precipitate. Injecting an acidic solution into the microchannels inside the hydrogel dissolves and removes the precipitate, allowing the electrochemical reaction to continue.
[0053] Step 5: When the surface roughness of the anode workpiece 2 meets the requirements, turn off the power, and the machining is complete.
[0054] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements can be made without departing from the principle of the present invention, and these improvements should also be considered within the scope of protection of the present invention.
Claims
1. A method for electrochemical polishing of hydrogel electrolytes with high localization, characterized in that, The method includes the following steps: (I) Construction of hydrogel electrolytes: (1.1) The hydrogel monomer is mixed with the crosslinking agent and subjected to freeze-thaw cycle treatment at low temperature. The monomer molecules will polymerize under the action of the crosslinking agent and solidify to obtain the hydrogel. The hydrogel has a three-dimensional network structure inside, which allows ion transport and ensures the smooth occurrence of electrochemical reactions. (1.2) Dense internal microchannels are fabricated for the solidified hydrogel; the dense microchannels allow acidic solutions to flow slowly through, ensuring that the precipitate generated during the processing is in full contact with the acidic solution; (ii) Highly localizable electrochemical polishing: (2.1) Place the hydrogel electrolyte between the anode and cathode, and use the pressure applied by the machine tool spindle to make the hydrogel and the anode and cathode interface fit tightly together. Adjust the position of the spindle to make the hydrogel and the anode and cathode interface in the best contact state. (2.2) The cathode is connected to the negative terminal of the power supply and the anode is connected to the positive terminal of the power supply. Due to the solid-like properties of the hydrogel electrolyte, the processing area is strictly limited to the contact area between the anode interface and the hydrogel. The anode material in the processing area dissolves due to electrochemical reaction. (2.3) Under the action of an external electric field, the anode dissolves, and metal ions enter the solution and migrate to the cathode; hydrogen evolution reaction occurs at the cathode to generate hydroxide ions, which migrate to the anode; metal ions combine with hydroxide ions to form a precipitate, which hinders the electrochemical reaction. (2.4) Inject an acidic solution into the microchannels inside the hydrogel. The acidic solution will dissolve and remove the precipitate in the hydrogel, allowing the electrochemical reaction to continue and completing the highly localized electrochemical polishing of the anode workpiece.
2. The method according to claim 1, characterized in that, The spatial constraint of the electrochemical reaction is achieved by using a solid-state hydrogel electrolyte; the gel is a network structure formed by cross-linking of hydrophilic polymer chains, which contains a large number of three-dimensional network structures to provide channels for ion migration.
3. The method according to claim 2, characterized in that; The hydrogel's solid-like properties restrict the electrochemical reaction to a localized area where it contacts the workpiece. During processing, the hydrogel is in close contact with the anode and cathode interfaces, with the cathode connected to the negative terminal of the power supply and the anode connected to the positive terminal. The anode material dissolves due to the electrochemical reaction. The dissolution products at the microscopic protrusions of the workpiece diffuse easily, resulting in a faster reaction rate. However, the products at the depressions accumulate significantly due to the longer diffusion path, leading to a slower reaction rate. This difference in dissolution rates results in the leveling of the anode surface.
4. The method according to claim 1, characterized in that, During the processing, it is necessary to ensure that the hydrogel adheres tightly to the anode and cathode. Therefore, the hydrogel should have good mechanical strength and toughness. The mechanical properties of the hydrogel are improved by constructing a dual network structure, increasing the crosslinking density, and using composite nanomaterials.
5. The method according to claim 1, characterized in that, Hydrogels are three-dimensional networks formed by hydrophilic monomeric polymer chains interconnected through cross-linking points, providing channels for ion migration; the conductivity of the hydrogel is improved by polymerizing conductive monomers, composite conductive fillers, and conductive ion permeation methods.
6. The method according to claim 1, characterized in that, The anode and cathode interfaces are tightly bonded to the hydrogel electrolyte under the pressure of the machine tool spindle to ensure the smooth progress of the electrochemical reaction. The pressure of the machine tool spindle should be less than the limit pressure that the hydrogel can withstand, while ensuring tight bonding between the hydrogel and the anode and cathode interfaces, to avoid damage to the hydrogel. The actual pressure value is observed by the machine tool spindle force sensor, and the spindle position is finely adjusted to achieve the best contact state between the hydrogel and the anode and cathode interfaces.
7. The method according to claim 1, characterized in that, During the processing, metal ions generated at the anode enter the hydrogel and migrate towards the cathode. The hydrogen evolution reaction at the cathode generates hydroxide ions, which migrate towards the anode. The metal ions and hydroxide ions form precipitates inside the hydrogel, hindering the continued electrochemical reaction. The hydrogel has dense micro-channels inside. During the processing, an acidic solution is injected into the channels to dissolve the precipitates and carry them out of the hydrogel.
8. The method according to claim 1, characterized in that, When energized, due to the solid-like properties of the hydrogel, the electrochemical reaction is strictly confined to the local area where the hydrogel contacts the workpiece. The anolyte in the processing area dissolves due to the electrochemical reaction. The dissolution products at the microscopic protrusions of the workpiece are easy to diffuse and the reaction rate is fast, while the products at the depressions are severely accumulated due to the long diffusion path and the reaction rate is slow. The difference in dissolution rate between the two leads to the leveling of the workpiece surface.
Citation Information
Patent Citations
System and method for improving locality of electrolytic processing of array micro-pit by flexible template
CN104551282A
Polishing component generating micro electrostatic field and chemical polishing equipment
CN105405791A
Magnetic polydimethylsiloxane (PDMS) mask-based micro-pit array electrolytic machining system and method
CN106064261A
A method for fabricating a hydrogel chip with a dendritic channel structure
CN108890937B
Device and method for particle-assisted mask electrolytic machining
CN111515480A
